Effects of Diversification, Bank Size and Bank Competition on Profitability of Islamic Banks - Ambawani, Firdaina Nanda Puan; Muharrami, Rais Sani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to analyse the effects of diversification, bank size and bank competition on the profitability of Islamic banks for the period 2019-2023. Methodology: The data was taken from the financial statements published on each bank's website, the Financial Services Authority (OJK), the Central Bureau of Statistics (BPS), and Bank Indonesia. This study uses quantitative research methods with a panel data regression approach. This study covers 10 Islamic banks with the largest assets from 2019-2023. Based on the criteria obtained through purposive sampling method, six samples or 30 data were obtained and data analysis was carried out using eviews 10. Results: Diversification increases the profitability of Islamic banks, with proper diversification banks will minimise the risk of dependence on one product. Bank Size and Bank Competition are negative indicating that in terms of assets and competition these six banks have not controlled the banking market share so that it does not affect the profitability of Islamic banks. Applications/Originality/Value: This study contributes not only to the existing literature, but also paves the way for further research exploring the interplay between diversification, bank size and bank competition in the Islamic banking sector.